The Role of the Controllership Regarding the Degree of Centralization of Organizations - Carlos Alberto Diehl (Revista Sociedade, Contabilidade e Gestão, 2012)
The aim of this paper is to discuss the role of controllership in organizations concerning the degree of centralization. For this purpose, a theoretical essay was developed in which the centralization and decentralization are discussed, addressing organizational structures, decision making and controllership. It was found that in organizations with a greater degree of centralization the accounting information system tends to be focused on the overall result of the organization, little oriented to the control of results and formed by non-financial and qualitative information. The budget tends to be used to indicate the distribution and tracking of expenditures. In organizations with a lower degree of centralization, there is a need for an information system oriented to the result of the divisions, with decentralized reports available to managers. The budget, in addition to indicating the destination of resources, must show the origin of the results, given that each divisional manager is responsible for the cost budgeting, revenues and investments of his/her division.